COMPRESSIVE STRENGTH OF GEOPOLYMER LIGHTWEIGHT CONCRETE WITH COMPARISON OF RICE HUSK ASH AND ALKALI ACTIVATOR 50% -50% IN CURING TIME VARIATIONS - KUKUH KURNIAWAN D.S; TEGUH YUONO (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2018)
Today, concrete is a very important building material material in construction. Geopolymers are concrete technologies that utilize polymerization reactions in the binding process. The main arrangement of this geoplimer material is silica and alumina (aluminum silica hydroxide). Silica material used is derived from inorganic materials that have high silica content. Rice husk ash is one of the industrial by-products that have high silica content. Rice husk ash resulting from burning bricks reaches a temperature of 400o C and has a silica content of around 85%. High silica content in rice husk ash can be used as a binding material in geopolymer concrete. The study carried out on lightweight geopolymer concrete rice husk ash with a ratio of rice husk and alkali activator ratio is 50%:50%, in the variation of curing time 12 hours and 24 hours. It was concluded that the compressive strength of geopolymer concrete from rice husk ash increases with the duration of curing time.